Comparison of Iconography in Shahnameh Tahmasp and Haft Orang of Jami - Afshari, Morteza; Dastmardi, Amir (Journal of History Culture and Art Research, 2017)
Special consideration of iconography by Iranian artist is one of the properties of Iranian painting. Paying attention to simplification of icons, proportions, clothes and more importantly, specific methods of Iranian artists in the field of iconography are issues that must be considered in depth in the studies related to Iranian painting. Mashhad Workshop is one of the Iranian painting schools established from the heart of Tabriz School II and the works created in this workshop are typically heir of Tabriz School II. Special features to previous works are evident in these works and it seems that these features can be observed in the icons and characterization in figures. In this study, through comparing Haft Orang of Jami from Mashhad's School and Shahnameh Tahmasp from Tabriz School II, these features are evaluated. In early investigations, it seemed that the artists of Haft Orang have sometimes followed the principles used in Shahnameh Tahmasp to draw configurations. Also, in most works, they tended to show various positions and characterizations through considering variety in the field of designing the icons.